MOTIVASI, PENGAJARAN, DAN PEMBELAJARAN - Safitri, Alya Nur; Ginting, Rahmadani Fitri (Sindoro: Cendikia Pendidikan, 2024)
This research examines the relationship between motivation, teaching, and learning in the context of effective education. Both intrinsic and extrinsic motivation play a key role in triggering students' interest and commitment to learning. We begin by exploring various theories of motivation, highlighting inherent needs such as competence, autonomy, and relatedness. Next, we analyze the teacher's role in fostering intrinsic motivation through student-centered teaching strategies, relevant curricula, and collaborative learning environments. Additionally, this study acknowledges the importance of extrinsic motivation, such as positive reinforcement and feedback, while emphasizing the need for balance to maintain intrinsic motivation. Learning is viewed as an active process in which students critically engage with information and construct their own understanding. This paper underscores the importance of creating learning environments that encourage exploration, collaboration, and inquiry. By understanding and leveraging the dynamic relationship between motivation, teaching, and learning, educators can create motivating and empowering learning spaces, enabling students to reach their full potential.”. Penelitian ini mengkaji hubungan antara motivasi, pengajaran, dan pembelajaran dalam konteks pendidikan yang efektif. Motivasi, baik intrinsik maupun ekstrinsik, memainkan peran kunci dalam memicu minat dan komitmen siswa untuk belajar. Kami memulai dengan meneliti berbagai teori motivasi, menyoroti kebutuhan bawaan seperti kompetensi, otonomi, dan keterkaitan. Selanjutnya, kami menganalisis peran guru dalam menumbuhkan motivasi intrinsik melalui strategi pengajaran yang berpusat pada siswa, kurikulum yang relevan, dan lingkungan belajar yang kolaboratif. Selain itu, penelitian ini mengakui pentingnya motivasi ekstrinsik, seperti penguatan positif dan umpan balik, serta tekanan perlunya keseimbangan untuk menjaga motivasi intrinsik. Pembelajaran dipandang sebagai proses aktif di mana siswa terlibat secara kritis dengan informasi dan membangun pemahaman mereka sendiri. Makalah pentingnya ini menciptakan lingkungan belajar yang mendorong eksplorasi, kolaborasi, dan pertanyaan. Dengan memahami dan memanfaatkan hubungan dinamis antara motivasi, pengajaran, dan pembelajaran, guru dapat menciptakan ruang belajar yang memotivasi dan memberdayakan, sehingga memungkinkan siswa mencapai potensi penuh mereka.